RESEARCH ON (WOMEN’S) SEXUALITY IN ISLAM - Irma Riyani (UIN Sunan Gunung Djati Bandung, 2014)
There are shared beliefs among Muslims in many Muslims countries in regard to theidea of sexuality in Islam. These beliefs may include that Islam views sex positively,which means that it recognises sex as part of human nature (fitrah), but should onlybe fulfilled in the institution of marriage, as marriage is the only institution to legallyhave sexual intercourse. Sex outside marital bond is considered zina. Heterosexual is the norm which means that any sexual practices and identities outside this norm are considered deviant. Men’s sexual desire is privileged, while women’s sexual desire is feared. Islam also recognises the purpose of sex within marriage as not only for procreation but also for pleasure.